2009
DOI: 10.1007/s10800-009-9897-z
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical reaction of biomass-related compounds in a biophotochemical cell comprising a nanoporous TiO2 film photoanode and an O2-reducing cathode

Abstract: Photoelectrochemical decomposition of biorelated compounds such as ammonia, formic acid, urea, alcohol, and glycine by a biophotochemical cell (BPCC) comprising a nanoporous TiO 2 film photoanode and an O 2 -reducing cathode generating simultaneously electrical power was investigated. The bio-related compounds studied were all photodecomposed by the present BPCC when they were either liquid or soluble in water. It was shown that ethanol exhibits similar characteristics both under 1 atm O 2 and air as studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…TiO 2 electrode (anode) is separated in a twocompartment cell from the counter electrode (cathode) by a Nafion membrane, irradiated by UV light and bias potential, such that oxidation could occur simultaneously on the anode and generate hydrogen on the cathode. The literature reports the use of ethanol, glycerol, and methanol or models of biomass compounds useful in photoelectrochemical incineration on the photoanode [117][118][119]. When this process occurs in a photoelectrocatalytic cell, a relatively large number of electrons should be conducted through the external circuit to reduce hydrogen ions and produce molecular hydrogen [13].…”
Section: Reactions Occurring In the Counter Electrode (Cathode)mentioning
confidence: 99%
“…TiO 2 electrode (anode) is separated in a twocompartment cell from the counter electrode (cathode) by a Nafion membrane, irradiated by UV light and bias potential, such that oxidation could occur simultaneously on the anode and generate hydrogen on the cathode. The literature reports the use of ethanol, glycerol, and methanol or models of biomass compounds useful in photoelectrochemical incineration on the photoanode [117][118][119]. When this process occurs in a photoelectrocatalytic cell, a relatively large number of electrons should be conducted through the external circuit to reduce hydrogen ions and produce molecular hydrogen [13].…”
Section: Reactions Occurring In the Counter Electrode (Cathode)mentioning
confidence: 99%
“…Then the cell acts as a Photofuelcell (PFC). This term, in this or in slightly modified form, is recently gaining more and more ground [13,14,17,[60][61][62][63][64]. A PFC consumes an Fig.…”
Section: The Photofuelcellmentioning
confidence: 99%
“…In the presence of oxygen, the cathode behaves as an oxygen electrode. Its potential is then affected by the following reductive reactions [61]:…”
Section: Basic Configuration Of a Pec Cellmentioning
confidence: 99%
“…A mesoporous TiO 2 showed a sharp increase of anodic photocurrent around the conduction band edge potential (E CB , -0.77 V vs. SHE at pH 12 [14]) reaching rapidly an equilibrium photocurrent in its cyclic voltammogram (CV) in an ammonia aqueous solution under UV irradiation [8]. Based on both this CV and a clear photovoltage-photocurrent characteristics with a high Fill Factor (0.65) for the TiO 2 photoanode/the O 2 -reducing cathode two-electrodes system, it was concluded that the nanoporous TiO 2 forms a kind of Schottky junction (called a liquid-junction) with an aqueous ammonia [8,15]. In a liquid-junction n-semiconductor photoelectrochemical system [1][2][3], excitation of electrons from the valence band (VB) to the conduction band (CB) takes place by irradiation of the semiconductor with the light whose energy is larger than the bandgap of the semiconductor, forming separated electrons (in the CB) and holes (in the VB), and thus separated charges can induce oxidation and reduction reactions at the photoanode and the cathode, respectively.…”
Section: Effect Of Cathode (Pt/fto)mentioning
confidence: 96%